The Contribution of Land Use Planning to Reducing Traffic Growth: the English Experience - Headicar, Peter (European Journal of Transport and Infrastructure Research, 2003)
The relationship between land use and travel behaviour has attracted research interest in England over the last fifteen years, principally in connection with possible links between urban form and sustainability. Since the mid 1990s this work has been overtaken somewhat by Government policy initiatives. This is something of a mixed blessing. Official attention has shifted to the implementation of what is now an established line of policy. In academic circles, by contrast, there is increasing interest in mobility more generally as a phenomenon of contemporary society. In this context the pattern of land use remains an important influence, if only because of the physical legacy presented by the established pattern of development. However, the evolution in travel behaviour is, as ever, conditioned by broader social and economic trends (Gillespie et al 1998). This paper provides an overview of English experience in this field in three main sections: research, policy and implementation. To place these in context they are preceded by a section titled 'background' which highlights for an international audience some of the distinctive features of the English scene, in terms of geography, cultural attitudes to development and travel, and institutional arrangements for land use and transport planning. These require very careful consideration before any attempt is made to draw inferences for policy-making in other countries.